Study of Viscosity Measurement by Curved Vibrating Wire Method - Saudiah Mawaddah; Elin Yusibani; Evi Yufita (PSI-Aceh, 2015)
A simple and compact sensor has been designed for measuring a viscosity of a fluid. The sensor consists of a magnet and a curved thin wire made of copper. The function generator supplies a frequency and the voltage output was reading by the lock-in amplifier. The measuring voltages were analyzed by the curve fitting method numerically.